Homeorresis generizadas: las diferencias atléticas conceptualizadas desde una perspectiva materialista no biologicista - Ciccia, Lucía (El Colegio de México A.C., 2022)
In this work I seek to problematize the idea that the binary distribution in athletic performance is due to differences in testosterone levels. Specifically, these would account for the higher proportion of lean muscle mass, bone density and hemoglobin concentrations which, in turn, would explain such distribution with the consequent male advantage. In contrast, I develop explanatory hypotheses that reinterpret the average differences in the aforementioned parameters and sports performance within the framework of gender regulations. Thus, I use the notion of homeorhesis to refer to the complex physiological processes through which our organisms stabilize, suggesting that they reflect gendered practices. In other words, I describe how we can molecularly materialize living from gendered bodies. Such a materialization, I suggest, may involve assuming as reference values biological differences that are not natural. Instead, they deal with standardized average values from androcentric biological interpretations that assume chronic deficit states for cis-women. I conclude that what a body can do is delineated by a testocentric discourse that interacts with our psychological / biological states—an interaction that leads to nocebo events for feminized bodies that participate in masculinized areas, such as competitive sport.